Willehalm—Genealogical Dimension of Sponsoring Poetry - Klára Berzeviczy; Gyula Pályi (Genealogy, 2023)
The medieval respect towards progenitors induced not only sentimental feelings but also practical steps, such as sponsoring works of art. In the present study, the family connections of Landgrave Hermann I of Thuringia to the Carolingians and to (Saint) Guillaume/Guilhem d’Orange, from the family of the Counts of Autun, have been explored. The possibility of the role of these kinships as a “driving force” behind initiating and sponsoring the epos Willehalm of Wolfram von Eschenbach has been analyzed.